2021
DOI: 10.1002/smll.202101770
|View full text |Cite
|
Sign up to set email alerts
|

A Membrane‐Targeting Photosensitizer with Aggregation‐Induced Emission Characteristics for Highly Efficient Photodynamic Combat of Human Coronaviruses

Abstract: COVID‐19 pandemic, caused by severe acute respiratory syndrome coronavirus 2, has resulted in global social and economic disruption, putting the world economy to the largest global recession since the Great Depression. To control the spread of COVID‐19, cutting off the transmission route is a critical step. In this work, the efficient inactivation of human coronavirus with photodynamic therapy (PDT) by employing photosensitizers with aggregation‐induced emission characteristics (DTTPB) is reported. DTTPB is de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 47 publications
(64 reference statements)
1
42
0
Order By: Relevance
“…PhytoQuin acts in a light-dependent manner to damage nearby macromolecules, which is consistent with a ROS-mediated mechanism of action as observed for other photosensitizers. Our study provides strong support for the addition of PhytoQuin and the PhytoQuin constituent emodin to the growing list of PSs with antiviral activity against CoVs [30][31][32][33][34][35][36][37].…”
Section: Discussionsupporting
confidence: 53%
“…PhytoQuin acts in a light-dependent manner to damage nearby macromolecules, which is consistent with a ROS-mediated mechanism of action as observed for other photosensitizers. Our study provides strong support for the addition of PhytoQuin and the PhytoQuin constituent emodin to the growing list of PSs with antiviral activity against CoVs [30][31][32][33][34][35][36][37].…”
Section: Discussionsupporting
confidence: 53%
“…6d). 113 DTTPB was constructed by linking two cationic AIE PS units together through a benzene ring. The hydrophobic parts of DTTPB could generate a hydrophobic interaction with the nonpolar tail of virus phospholipids, while the hydrophilic ones could align on lipid bilayer surfaces of the viruses through electrostatic interactions.…”
Section: Molecular Systemsmentioning
confidence: 99%
“…Previously, we demonstrated that DTTPB exerted neglectable influence on cells by employing CCK 8 experiments. [40] In this work, we further evaluated its biocompatibility by conducting a hemolysis experiment and fluorescence staining. For comparison, the biocompatibility of 5% H 2 O 2 was also evaluated under the same experimental conditions (Figure 6, Figures S15 and S16, Supporting Information).…”
Section: Biocompatibilitymentioning
confidence: 99%